Force plate vertical jump scans are not a valid proxy for physical fitness in US special warfare trainees - Scott, W. Casan; Hando, Ben R.; Butler, Cody R.; Mata, John D.; Bryant, Jacob F.; Angadi, Siddhartha S. (Frontiers in Physiology, 2022)
Background: The United States Air Force (USAF) Special Warfare Training Wing (SWTW) administers a comprehensive physical fitness test to active duty Airmen entering the SW training pipeline. The Sparta Science™ system utilizes proprietary software to analyze the force-time curve of a vertical jump and purports to serve as a proxy for traditional military fitness tests. The Sparta Science™ system produces four proprietary metrics, including the Sparta™ Score, which is correlated to high magnitudes of force production purportedly performance. This study investigated how Sparta™ Jump Scans correlate to components of a physical fitness test utilized within the SW training pipeline. Methods: At the entry and exit of an 8-week SWTW preparatory course (SW PREP), 643 trainees completed both an initial and final Sparta™ Jump Scan and an Candidate Fitness Test (CFT). The CFT consists of eight components and tests several different domains of fitness including strength, power, muscular endurance, swimming proficiency, and cardiovascular fitness. Paired t-tests were used to determine if Sparta™ Jump Scan metrics and CFT components changed during SW PREP. Sparta™ Score’s correlation was assessed against every other Sparta™ Jump Scan metric and all CFT fitness measures. Results: This study found that the Sparta™ Jump Scan metrics decline slightly over SW PREP (p < 0.05; negligible-small effect size), while most CFT measures improve (p< 0.05; small-medium effect size). Changes in Sparta™ Jump Scan metrics did not reflect the changes in CFT performance over SW PREP (r2: 0.00 – 0.03). Conclusion: The Sparta™ Score was not correlated to the most tactically-relevant fitness measures (rucking and swimming), and only weakly correlated with the only jumping measure on the fitness test, the standing broad jump.